Revisiting the Model Human Processor: a neurophysiological investigation based on P300 and Bereitschaftspotential - Higashino, Toshitaka; Wakamiya, Naoki (Frontiers in Human Neuroscience, 2025)
IntroductionThe Model Human Processor (MHP), while useful, lacks direct neurophysiological validation. This study aimed to validate and extend the MHP by analyzing P300 and Bereitschaftspotential (BP) brainwave components.MethodsOur initial finding of qualitatively different neural signatures between correct and incorrect trials led to the hypothesis that the “correct” trial group is a mixture of different processing types. We tested this by segregating correct trials based on the presence or absence of the P300 component, which we reasoned is a key marker of the MHP’s conscious “Initiate Response” process.ResultsWe identified a P300-absent subgroup even among correct responses. This subgroup exhibited significantly shorter reaction times than its P300-present counterpart and showed a neural signature strikingly similar to that of incorrect trials, including a delayed negative peak in the BP.DiscussionThese results suggest the human information processing pathway is not monolithic. We propose a new model that bifurcates after perception into either a “Deliberate Process” (P300-present), which aligns with the MHP, or a high-speed “Automatic Process” (P300-absent) that bypasses the MHP’s “Initiate Response” process. This work provides neurophysiological validation for the MHP and lends new neural support for dual-process theory.